Contact stress evaluation of involute gear pairs, including the effects of friction and helix angle - Patil, S.S. (American Society of Mechanical Engineers (ASME), 2015)
The aim of this technical brief is to provide a new viewpoint of friction factor for contact stress calculations of gears. The idea of friction factor has been coined, for the calculation of contact stresses along the tooth contact for different helical gear pairs. Friction factors were developed by evaluating contact stresses with and without friction for different gear pairs. In this paper, three-dimensional (3D) finite element method (FEM) and Lagrange multiplier algorithm have been used to evaluate the contact stresses. Initially, a spur gear finite element (FE) model was validated with the theoretical analysis under frictionless condition, which is based on Hertz's contact theory. Then, similar FE models were constructed for 5Ã¢â¬â°deg, 15Ã¢â¬â°deg, 25Ã¢â¬â°deg, and 35Ã¢â¬â°deg helical gear pairs. The contact stresses of these models were evaluated for different coefficients of friction. These results were employed for the development of friction factor.